Praktek Apptita’galak Tana (Gadai Sawah) dalam Perspektif Akuntansi Syariah - Wa Jana; Khairunnisa Kahar; Teguh Setiawan; Nina Yustina; Rahayu Indriasari; Andi Chairil Furqan (Akuntansi, 2024)
Abstract. This research aims to explore the meaning of informants' experiences in the practice of pawning, analyze the relationship between relevant statements, and describe the practice of pawning rice fields from the perspective of local wisdom values based on the provisions of Islamic sharia. The method used in this research is a qualitative approach with the phenomenological method. The research was conducted for approximately 3 (three) months (January-March 2022) in Bontolangkasa village. Appita'galak Tana means turning cultivated rice fields into collateral to get funds quickly. The values of tolerance and solidarity that underlie the practice of Appita' galak tana in Bontolangkasa village are a manifestation of the pacce values of the Bugis people to strengthen brotherhood through strong tolerance and solidarity. The appita'galak tana transaction has met the required criteria, namely that there is a debt transaction that was carried out because of the need for funds and no recording was carried out and there were no witnesses, where only two parties transacted, the land owner and the capital owner and were in a state of mind. There is a deviation in the practice of appita'galak tana that cannot be tolerated, namely the use of pawned goods by murtahin. Where the use of pawned goods is caused by borrowing money. This action includes usury an-nasiah even though the land/rice field pawning transaction already has permission from rahin.